Analysis of Price Volatility and Downstream Strategy for Shallot Price Stability in Java Island - Ardito Bhinadi; Bulan Lestari Yasinta Simatupang (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
Shallots are one of the horticultural products of seasonal crops whose prices have high volatility. Shallots are one of the commodities contributing to inflation in Java. This study aims to analyze the volatility and disparity of shallot prices in Indonesia in 2019-2024, focusing on provincial areas in Java. The analysis tools used price disparity, the food price variation coefficient, and importance-performance analysis. The study results show significant price fluctuations across different regions in Java. Shallot prices in Banten Province are elevated because of insufficient local supply. The price of shallots in East Java Province, which serves as the primary production center, tends to be lower than in other Java provinces. This study identifies the need for downstream processes as a strategic step to stabilize shallot prices. According to this study, improving infrastructure, research and development (RD), and price stability measures is imperative to lower shallot price volatility, guarantee higher farmer earnings, and guarantee that consumers experience more stable pricing. Agriculture downstream is a crucial strategy to overcome shallot price volatility and improve overall supply chain efficiency.